2012
DOI: 10.1002/da.21921
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity in Adolescence and Young Adulthood: The Role of Stressful Life Events, 5httlpr and Their Interaction

Abstract: Background: Cognitive biases have long been hypothesized to influence the development and maintenance of symptoms of internalizing problems. Anxiety sensitivity represents one such bias and refers to sensitivity to the physical and emotional symptoms of anxiety and the belief that these are harmful. Twin studies indicate a role for both environmental and genetic influences on anxiety sensitivity. However, little work has been done specifying environments or genes involved in this phenotype. In light of this, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 44 publications
1
25
0
1
Order By: Relevance
“…When people experiencing high anxiety become anxious, they pay greater attention to their arousal-related sensations and this further amplifies their anxiety. This finding is consolidated by the evidence showing that people having various types of anxiety disorders experience more anxiety sensitivity when compared to control participants and the higher the current level of anxiety, the higher the risk for displaying future anxiety symptoms [37,64].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…When people experiencing high anxiety become anxious, they pay greater attention to their arousal-related sensations and this further amplifies their anxiety. This finding is consolidated by the evidence showing that people having various types of anxiety disorders experience more anxiety sensitivity when compared to control participants and the higher the current level of anxiety, the higher the risk for displaying future anxiety symptoms [37,64].…”
Section: Introductionmentioning
confidence: 93%
“…Anxiety sensitivity contributes to the differences observed in the extent to which general fearfulness is experienced by different individuals and in the extent to which tendency for various types of anxiety disorders such as panic disorder, social anxiety disorder, specific phobia, and posttraumatic stress disorder exhibited by different individuals [34,36,37,50,64,65]. When people experiencing high anxiety become anxious, they pay greater attention to their arousal-related sensations and this further amplifies their anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to candidate gene studies reviewed above, G × E studies mainly focus on the serotonin, hypothalamic–pituitary–adrenal (HPA) axis (e.g., CRHR1 ), and neurotrophin systems (e.g., BDNF ) in predicting AD. The most extensively investigated gene in relation to environment is serotonin transporter ( SLC6A4 , its functional promoter length polymorphism 5‐HTTLPR ) . Gunthert et al .…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…The most extensively investigated gene in relation to environment is serotonin transporter (SLC6A4, its functional promoter length polymorphism 5-HTTLPR). [53][54][55][56][57] Gunthert et al and Stein et al reported that the short variant modified the effect of current daily stress or previous childhood maltreatment on anxiety sensitivity, which may be a potential endophenotype of AD. 53,56 In contrast, Klauke et al and Laucht et al reported that long allele homozygotes with childhood maltreatment or family adversity displayed higher anxiety sensitivity and AD rates, respectively.…”
Section: Gene × Environmental Interactionmentioning
confidence: 99%
“…Moreover, AS is thought to be interactively impacted by additive genetic factors as well as unique environmental factors (Garcia et al, 2013; Stein et al, 1999), such as stressful life events (Aktekin et al, 2001; Zavos et al, 2012), including CM and severe family conflict (McLaughlin & Hatzenbuehler, 2009; Scher & Stein, 2003), demonstrating the interactive effect of genes and environment on AS.…”
Section: Introductionmentioning
confidence: 99%